INQUILAB : BHAGAT SINGH ON RELIGION AND REVOLUTION - S IRFAN HABIB (NEW DELHI SAGE, 2018)
Puts forward the revolutionary freedom fighter Bhagat Singh's vision for independent India through some of his most relevant writings for our times.
Keywords: BHAGAT SINGH - POLITICAL AND SOCIAL VIEWS; RELIGION AND POLITICS-INDIA; REVOLUTIONS